If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 = 6t + -19t Combine like terms: 6t + -19t = -13t 65 = -13t Solving 65 = -13t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '13t' to each side of the equation. 65 + 13t = -13t + 13t Combine like terms: -13t + 13t = 0 65 + 13t = 0 Add '-65' to each side of the equation. 65 + -65 + 13t = 0 + -65 Combine like terms: 65 + -65 = 0 0 + 13t = 0 + -65 13t = 0 + -65 Combine like terms: 0 + -65 = -65 13t = -65 Divide each side by '13'. t = -5 Simplifying t = -5
| 8x+5x+3=x-4+7 | | 5(6y-3)=15y | | 6n+5N= | | x+7=2x+5 | | X^2=66-5x | | 24g-22=2g | | x/3-10=2x | | 0.04(4c-92)=-0.8(c-5) | | -5x-5x=9-4 | | 2/3x=2y-2/5 | | -3(y+3)=-2y+3 | | X^2+5x=16 | | 4x+14-3x=-6-13 | | 12x+9=2x+9 | | X^2-3x-66=0 | | 10x+12=3(3x+2) | | 8x+8+7=5x+12+3x | | 3/2r-7(-17/6r+5/4)=349/4 | | 64X^2Y^3-8X^2=0 | | 8x+16-7x=-2-10 | | -(3x-3)-(10x-6)+8=-4(x-1)-(14x+5)+3 | | 9=-7+1-6 | | -y-5=-9 | | 5(x-8)+x=6(x-8)+8 | | 11x+29y=-13 | | n+7n/5=72 | | 5x+15-4x=-6-12 | | 3/x=13/5x+2 | | 15w^3+14w^2-8w=0 | | -18-6k=6(1+2k) | | 17x=16x-24 | | 7(2x+3)=7 |